The effectiveness of extracorporeal shockwave therapy on hypertrophic scar appearance and hand mobility in a severe burn patient - S.Y.J. Chan (Elsevier, 2020)
Background: After a burn injury, the development of hypertrophic scars may limit the ranges of movement of the involved joints and cause severe disturbance to appearance and daily function of the patient, especially when the burn region involves hands. The use of extracorporeal shockwave therapy (ESWT) on the treatment of hypertrophic scars has been risen in the recent decade. The most recent systematic review by Aguilera-Sáez et al. has demonstrated improvements in hypertrophic scar appearance, pain and pruritus after a course of ESWT. Hence, ESWT was included in treating our severe burn case. Objectives: To share the local experience and evaluate the effectiveness of ESWT on hypertrophic scar appearance and functional hand mobility in a severe burn patient. Methods: A patient suffered from a flame burn involving 27% total body surface area and predominantly full thickness skin burn was recruited at a local physiotherapy out-patient clinic. At post-injury 4 months, right hand flexor retinaculum and left 2nd-5th metacarpophalangeal joints (MCPJs) were chosen as the ESWT sites due to contractures limiting mobility and hand function. At a frequency of once to twice per week, 13 sessions with 2000 shots each session were performed on the right hand flexor retinaculum over 10 weeks, whilst 10 sessions with 1000 shots at each MCPJ per session were done on the left hand across 8 weeks. The parameters of ESWT were: 0 mm penetration depth, 0.124-0.142 J/mm2 energy flux density, and 8 Hz frequency. The outcomes were measured at pre- and post-treatment course of ESWT. The primary outcome measure was the scar appearance measured by Vancouver Scar Scale (VSS). The secondary outcome measure was the functional ranges of movement of fingers, Kapandji score and Patient-Specific Functional Scale (PSFS). Results: A marked improvement in scar appearance on clinical photos was shown on both hands after a course of ESWT with 2 to 3-point deduction on VSS. On the scale of modified VSS, the 6-point reduction on the right hand scar exceeded the minimal clinically important difference (MCID), while the left hand scar also showed a 2-point improvement. Fingers' ranges of movements also increased by 5 cm in thumb abduction, 20 degrees in MCPJs' flexion and 3 points in Kapandji score. The patient regained the ability to grasp a cup with 5-mark improvement in PSFS exceeding the MCID. Conclusion: The use of ESWT on the hypertrophic scar improves scar appearance and functional mobility in a severe burn patient. ESWT on burn patients should be considered as one of the treatment modalities and the field for further research. Keywords: Burn, ESWT, Shockwave, Scar, Hand, Physiotherapy